A new species of the lowland Oligosarcus Günther species group (Teleostei: Ostariophysi: Characidae) - Menezes,Naércio Aquino (2015)
A new characid species is described from the rio Jacuí basin, a coastal drainage from southern Brazil. Itis morphologically most similar to its sympatric congeners Oligosarcus jenynsii and O. jacuiensis , but can be distinguished from both species in having the interorbital region wider and the pectoral fin shorter and additionally from O. jenynsii in having a smaller orbital diameter.